Mapping candidate regions and genes for congenital anomalies of the kidneys and urinary tract (CAKUT) by array-based comparative genomic hybridization - Weber, Stefanie; Landwehr, Christina; Renkert-Baudis, Miriam; Hoischen, Alexander; Wühl, Elke; Denecke, Jonas; Radlwimmer, Bernhard; Haffner, Dieter; Schaefer, Franz; Weber, Ruthild (Nephrology, dialysis, transplantation, 2011)
Background. Congenital anomalies of the kidneys and urinary tract (CAKUT) are frequently associated with malformations of other organs.Methods. In order to explore the role of DNA microimbalances in syndromal CAKUT, we applied genome-wide array-based comparative genomic hybridization (array-CGH) in 30 children with various CAKUT phenotypes and at least one additional extrarenal symptom.Results. In three patients, causal imbalances were detected: In one patient with duplex kidney and vesico-ureteral reflux associated with extrarenal stigmata, a terminal 9.52 Mb gain in chromosomal band 2q37.1-q37.3 and a terminal 5.65 Mb loss in 7q36.2-q36.3 were detected, which were due to an unbalanced 2;7-translocation according to FISH analysis. A balanced 2;7-translocation was present in the unaffected mother. In another patient presenting with renal hypoplasia and proximal ureteric stenosis combined with mental retardation, macrocephaly and ear anomalies, a duplication of 2.73 Mb was detected in 1q21.1. The unaffected father had a 1.3 Mb gain in 1q21.1-q21.2 involving the distal part of the patient’s gain, for which benign copy number variation was described. A third patient affected by dysplastic kidney with a strongly dilated ureter and extrarenal abnormalities exhibited a de novo loss of 13.38 Mb in 3q23-q25.1 including the AGTR1 gene. However, no AGTR1 mutations were identified in the remaining allele of this case or in 108 patients with isolated renal dysplasia/hypoplasia.Conclusions. In this study, 10% of patients with syndromic CAKUT were shown to carry DNA microimbalances, and four chromosomal regions presumably associated with the CAKUT phenotype were identified: 1q21.1, 2q37.1-q37.3, 3q23-q25.1 and 7q36.2-q36.3.
Online veröffentlicht 5 July 2010
Gesehen am 11.11.2022